Who speaks for Hume: Hume's presence in the 'Dialogues concerning Natural religion' - Davidović Aleksandra (Belgrade Philosophical Annual, 2021)
One of the reasons for many different and even opposing interpretations of Hume's Dialogues Concerning Natural Religion is the absence of consensus concerning the question of which character in the Dialogues represents Hume. In this paper I argue that taking Philo to be his primary spokesperson provides us with the most consistent reading of the whole work and helps us better understand Hume's religious viewpoint. I first stress the specific dialogue form of Hume's work, which requires us to take into account literary tools such as irony and double-talk when interpreting it. From there I proceed to show why I believe that my hypothesis is better supported than the other two main hypotheses concerning Hume's presence in the Dialogues, the first one being that Cleanthes represents Hume and the other one that none of the characters consistently speaks for Hume but rather that the whole structure of the work does that. Although there is both textual and historical evidence which suggests that Hume favoured Cleanthes, I show that his opinions deviate from Hume's well-known views on important subjects such as scepticism, morality and Christianity, while Philo's opinions on these subjects agree with Hume's almost verbatim. The second hypothesis is proven to be wrong by the fact that Philo actually consistently defends Hume's opinions. Finally, I argue that Philo's understanding of true religion as a philosophical position devoid of any religious import agrees with Hume's religious scepticism.